De-imperializing Joseph Brodsky: "On the independence of Ukraine" and other poems. - Desnitsky, Andrei (Studies in East European Thought, 2024)
This article discusses the poem written by Joseph Brodsky shortly after the proclamation of Ukrainian independence in the early 1990s. It compares this poem with other pieces by the same author that deal with the paradigm of "independence vs. imperial unity." These poems present a difference, which is striking at first glance: Brodsky welcomes Lithuanian independence, while simultaneously denying the same rights to Ukrainians and Aztecs. As for Afghanis ... his disdain is even more palpable. The proposed explanation is the concept of "Cultural Empire," which the poet considers to be the ultimate good. This article briefly mentions the general problem of de-imperializing classical Russian literature in the context of post-colonial studies.